AB0707 Arthritis prevalence and biological markers in primary sjÖgren's syndrome. (23rd January 2014) - Solans-Laqué, R.; Sellas, A.; Ramentol, M.; Rodriguez-Fernandez, B.; Martinez-Valle, F.; Barcelo, M.; Farietta, S.; Bosch, J.A.
Abstract : Background: Primary Sjögren (pSS) is a chronic inflammatory autoimmune disease characterised by lymphocytic infiltration of the exocrine glands. Most patients present Keratoconjuntivitis sicca and xerostomia, and about 40% of them develop musculoskeletal manifestations, the most common being arthralgia and intermittent non-erosive polyarthropathy involving mainly the small joints. Rheumatoid factor (RF) is positive in more than 50% of p-SS patients, but cyclic citrullinated peptide antibodies (anti-CCP) are positive in less than 10% of cases. In rheumatoid arthritis (RA) presence and titre of anti-CCP have been related to the presence of shared epitope (SE). There are no available data in pSS. Objectives: To describe the prevalence of arthritis in a large cohort of patients with pSS, and to investigate whether a relationship exists between the presence of arthritis and positive RF, positive anti-CCP or SE. Methods: All patients diagnosed as having pSS at our Center between January 1988 and December 2010 who fulfilled the American-European Consensus Group diagnostic criteria were included. Levels of IgM RF >30 UI/mL and IgG anti-CCP >10 UI/mL were considered positive. HLA typing for the MHC class I and II was determined. Standard radiographs of hands and feet were reviewed to evaluate the presence of bone erosions, by three rheumatologists. Results: 250 pSS patients were included. The prevalence of arthritis was of 26.8%. RF and anti-CCP were determined in all cases. Hands and feet x-ray of were performed in all patients with arthritis and in all patients with positive anti-CCP. The MHC class I and II were determined in 43 patients. RF was positive in 115 (46%) cases and anti-CCP in 9 (3.6%). Seven of the 9 patients with positive anti-CCP suffered arthritis and 3 developed radiographic bone erosions after a long follow-up. The MHC class II antigen DRB1* 01 01 (SE) was present in all 3 cases. Conclusions: Almost a quarter of patients with pSS develop arthritis that usually is non-erosive and mainly involves small joints. The picture may mimic RA as more than 50% of patients with pSS are RF-positive. Anti-CCP antibodies are present in 10-12% of pSS patients and seem to be closely associated with the presence of arthritis. However, anti-CCP could not be employed as a predictor of future progress to RA. In these cases presence of SE may suggest a real overlap syndrome between pSS and RA and not a misdiagnosed RA. References: Atzeni F, Sarzi-Puttini P, Lama N, et al.Anti-cyclic citrullinated peptide antibodies in primary Sjögren syndrome may be associated with non-erosive synovitis. Arthritis Res Ther 2008; 10: 1-6. Fauchais AL, Ouattara B, Gondran G, et al.Articular manifestations in primary Sjögren's syndrome: cliical significance and prognosis of 188 patients. Rheumatology 2010; 49: 1164-72. Gottenberg JE, Mignot S, Nicaise-Rolland P, et al. Prevalence of anti-cyclic citrullinated peptide and anti-keratin antibodies in patients with primary Sjögren's syndrome. Ann Rheum Dis 2005, 64:114-117. Disclosure of Interest: None Declared